Bridging the gaps: Advancing clinical informatics, data science, and global health with ICD-11 - Jakob, Robert (Informatics and Health, 2026)
•ICD-11 is WHO’s first digital-native, ontology-based classification—linking informatics, data science, and health.•Over 180 countries are already on the ICD-11 journey, with 70 in advanced rollout or live-data stages.•ICD-11's API integrates with EHRs, enabling real-time analytics and AI insights.•ICD-11 includes extensive scientific and clinical updates across all chapters.•Postcoordination, extension codes and the foundation terminology provide unmatched detail for clinical coding, financing, and policy.•ICD-11 is available in 14 translations, with 22 underway, making it a global multilingual interoperable health data standard.